Bushfires in Tasmania, Australia: An Introduction - Bowman, David M. J. S.; Kolden, Crystal A.; Williamson, Grant J. (Fire (Basel, Switzerland), 2022)
The effect of vegetation patterns is not only related to changed fire regimes following the extirpation of Tasmanian Aboriginal people from traditional lands, but also to substantial ecological knock-on effects associated with changed ignition patterns and altered fuel loads stemming from resource exploitation (prospecting, land clearing, pastoralism, forestry) and increased human population densities. Like much of the world, the climate of Tasmania is changing due to anthropogenic greenhouse gas emissions. Since the 1950s, mean annual air temperatures have risen by 0.10 °C per decade, and since the mid 1970s, rainfall has declined across Tasmania, particularly in autumn months [15]. There is emerging evidence of a change in fire activity, with a steady increase since the 1990s in the number and the extent of bushfires ignited by lightning storms [18]. Since 1990, there has been a steady increase in the area of Tasmania burned by landscape fires, amounting to entirely one quarter of the island (Figure 2). Since the beginning of this century, there have been three particularly active and high-impact fire seasons in Tasmania: 2012–2013, 2015–2016 and 2018–2019.